Biocontrol potential of Beauveria bassiana and Metarhizium anisopliae isolates from Turkey against Hyphantria cunea (Drury) (Lepidoptera: arctiidae) Larvae under laboratory and field conditions (Bioscience Journal, 2022)
Hyphantria cunea is one of the most important pest insects causing significant damage in many plant species. The present study aimed to evaluate the insecticidal activity of Turkey isolates of Beauveria bassiana and Metarhizium anisopliae against H. cunea larvae under laboratory and field conditions. B. bassiana isolates YK16, YK23 and YK26, and M. anisopliae isolates YK41 and YK45 were sprayed onto the larvae of H. cunea at the respective doses of 1x105 and 1x106 conidia mL-1 and monitored for seven days. Fungal isolates, bio-insecticide Bacillus thuringiensis and chemical insecticide diflubenzuron were used in field studies. Trials were carried out in five replications. All B. bassiana isolates caused 100% mortality on first instar larvae in laboratory trials. Mortality ratios ranged from 100 to 96% on second instar larvae. M. anisopliae isolates YK45 and YK41 caused 88 and 84%, and 81.33 and 77.11% mortalities for the first and second instar larvae, respectively. The mortality rates fluctuated between 91.78-72.89% for B. bassiana on third instar larvae in laboratory conditions. However, M. anisopliae isolates YK45 and YK41 caused 77.11 and 60.22% mortality on third instar larvae, respectively. In the field trials, B. bassiana YK23 displayed promising insecticidal activity with 80.60% mortality on second instar larvae of H. cunea. Other isolates as well caused mortalities ranging from 60.77 to 49.55%. The results revealed that some isolates of B. bassiana and M. anisopliae have potential to control H. cunea larvae. However, additional detailed studies need to be carried out to increase their effectiveness in field conditions.